Optimalisasi Penyaluran Zakat Di Masyarakat: Studi Tentang Sistem Distribusi Syariah Lembaga Amil Zakat di Ponorogo - Dewi, Arlinta Prasetian (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
This research was conducted at several amil zakat institutions representing the Ponorogo area, namely BMH Ponorogo, LAZISMU ponorogo, BAZNAS Ponorogo Regency and LAZ Ummat Sejahtera. The location is adjusted to the origin of the institution. BMH and LAZISMU are under the auspices of the organization Hidayatullah and Muhamadiyah, BAZNAS under the auspices of the government in this case the ministry of religion, and LAZ Prosperous Community which is an independent institution. This research is qualitative descriptive field research. Methods of collecting data through observation, documentation, and interviews. While the type of data used is primary data and secondary data. From this study, it was concluded that the pattern of zakat distribution carried out by BMH and LAZ Prosperous Ummah could be said to be better and more innovative especially with the high professionalism of amil in work so that the distribution system could be optimally implemented, complete and organized in the hope that distribution could be optimized zakat institutions for the welfare of society will be greater.